Knockdown of Lumican Inhibits Proliferation and Migration of Bladder Cancer - Mao, Weipu (Transl Oncol, 2019)
Lumican (LUM) is differentially expressed between normal and cancer tissues. The purpose of this study was to investigate the role of LUM in the proliferation and migration of bladder cancer (BCa) cells. Our study included 97 cases of BCa diagnosis from our hospital between June 2013 and June 2016. The expression of LUM was analyzed by immunohistochemistry and Western blot. To characterize the function of LUM, BCa cells were stably infected with a lentivirus against LUM, and cell proliferation, migration and cell cycle were investigated. In addition, xenograft experiments were performed in nude mice to evaluate the role of LUM in BCa. Our results showed that LUM was overexpressed in BCa tissues and cell lines in comparison to normal tissues. LUM expression was related to pathological type, T stage and N stage (P < .05). In addition, depletion of LUM inhibited the proliferation and migration of BCa cells by inactivating MAPK signaling. In conclusion, LUM promotes the proliferation and migration of BCa cells and may serve as a potential therapeutic target for BCa.